Coronavirus in the (bio)political imaginarium - Perić Diligenski, Tijana D. (Sociološki pregled, 2020)
The paper starts from the premise that (bio)political engineering of conservatively profiled political actors during the coronavirus (SARS-CoV-2) pandemic was determined by economic calculations. The coronavirus imaginarium exposed the logic of the neoliberal market economy and pointed to the need to deconstruct the existing and establish a new economic paradigm. The findings of the paper show that the pandemic has brought to light an infection of non-solidarity and intolerance towards the phenomenon of otherness, which is accused of being a contagious factor. The paper elaborates that democratic ways of governing are overshadowed by populist manners that tend to use the narrative of fear of viruses to consolidate their own regimes.
Keywords: biopolitics; coronavirus; pandemic; quarantine; life